Metatranscriptomic Signatures Associated With Phytoplankton Regime Shift From Diatom Dominance to a Dinoflagellate Bloom - Zhang, Yaqun; Lin, Xin; Shi, Xinguo; Lin, Lingxiao; Luo, Hao; Li, Ling; Lin, Senjie (Frontiers in Microbiology, 2019)
Diatoms and dinoflagellates dominate coastal marine phytoplankton communities as major players of marine biogeochemical cycles and their seasonal succession often leads to harmful algal blooms (HABs). What regulates their respective dominances and the development of the HABs remains elusive. Here we conducted time-sequential metatranscriptomic profiling on a natural assemblage that evolved from diatom dominance to a dinoflagellate bloom to interrogate the underlying major metabolic and ecological drivers. Data reveals similarity between diatoms and dinoflagellates in exhibiting high capacities of energy production, nutrient acquisition, and stress protection in their respective dominance stages. The diatom-to-dinoflagellate succession coincided with an increase in turbidity and sharp declines in silicate and phosphate availability, concomitant with the transcriptomic shift from expression of silicate uptake and urea utilization genes in diatoms to that of genes for light harvesting, diversified phosphorus acquisition and autophagy-based internal nutrient recycling in dinoflagellates. Furthermore, the diatom-dominant community featured strong potential to carbohydrate metabolism and a strikingly high expression of trypsin potentially promoting frustule building. In contrast, the dinoflagellate bloom featured elevated expression of xanthorhodopsin, and antimicrobial defensin genes, indicating potential importance of energy harnessing and microbial defense in bloom development. This study sheds light on mechanisms potentially governing diatom- and dinoflagellate-dominance and regulating bloom development in the natural environment and raises new questions to be addressed in future studies.